Development of Mathematics Learning Videos Using Filmora to Improve Learning Outcomes for Class VIII Students of Middle School - Nurliani Manurung; Inez Laurencia Simbolon (Formosa Journal of Multidisciplinary Research, 2023)
The purpose of this study was to find out the validity, practicality, and find out the increase in student learning outcomes from mathematics learning videos using Filmora on statistics material for class VIII SMP Negeri 1 Onanarugu. This type of research is research and development (Research and Development) which uses the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The subjects in this study were class VIII-2 of SMP Negeri 1 Onanrunggu T.A. 2022/2023. The trial was conducted on 25 students. The instruments used in this study were (1) questionnaires validating learning media and questionnaires on learning media materials; (2) questionnaires on the practicality of learning videos by teachers and students; and (3) pretest and posttest questions. The results of the study show that the mathematics learning video using the developed Filmora is valid and feasible to use. This can be seen from the results of the assessment given by media experts with an average score of 3.8 and the results of the assessment by material experts with an average of 3.9, namely in the "very decent" category. The learning videos developed are also practical. The results of the practicality assessment by the teacher were obtained with a final mean of 4.00 and a final mean score of practicality by students of 3.45 in the "very practical" category. The effectiveness of learning videos is seen from the increase in student learning outcomes as seen from classical learning outcomes, namely as much as 84%.